2001
DOI: 10.1021/ac0101095
|View full text |Cite
|
Sign up to set email alerts
|

Charge-State-Dependent Sequence Analysis of Protonated Ubiquitin Ions via Ion Trap Tandem Mass Spectrometry

Abstract: One of the major factors governing the "top-down" sequence analysis of intact multiply protonated proteins by tandem mass spectrometry is the effect of the precursor ion charge state on the formation of product ions. To more fully understand this effect, electrospray ionization coupled to a quadrupole ion trap mass spectrometer, collision-induced dissociation, and gas-phase ion/ion reactions have been employed to examine the fragmentation of the [M + 12H]12+ to [M + H]+ ions of bovine ubiquitin. At low charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
271
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 164 publications
(299 citation statements)
references
References 73 publications
27
271
1
Order By: Relevance
“…Ion/ion reactions provide efficient means for manipulating the identities of gas-phase ions after their initial formation [3,4], including altering ion polarity and absolute charge. Applications of charge manipulation via ion/ ion reactions include: mixture analysis [5][6][7][8], especially with the application of the "ion parking" technique for gas-phase concentration and charge state purification [9], the formation of ions that cannot be directly produced by ESI for subsequent tandem mass spectrometry studies [10], and the reduction of the product ion charge states to singly and doubly charged so as to simplify the interpretation of product ion spectra [11][12][13][14][15][16]. Electron-transfer ion/ion reactions have recently been described as a means of inducing structurally informative dissociation, giving rise to cleavages analogous to those noted in electron capture dissociation [17][18][19][20][21].…”
mentioning
confidence: 99%
“…Ion/ion reactions provide efficient means for manipulating the identities of gas-phase ions after their initial formation [3,4], including altering ion polarity and absolute charge. Applications of charge manipulation via ion/ ion reactions include: mixture analysis [5][6][7][8], especially with the application of the "ion parking" technique for gas-phase concentration and charge state purification [9], the formation of ions that cannot be directly produced by ESI for subsequent tandem mass spectrometry studies [10], and the reduction of the product ion charge states to singly and doubly charged so as to simplify the interpretation of product ion spectra [11][12][13][14][15][16]. Electron-transfer ion/ion reactions have recently been described as a means of inducing structurally informative dissociation, giving rise to cleavages analogous to those noted in electron capture dissociation [17][18][19][20][21].…”
mentioning
confidence: 99%
“…In addition to chemical probes of gas phase ion structure [1][2][3][4][5][6][7][8][9][10][11][12][13][14], a number physical methods are being developed to examine gas-phase peptide and protein ion structure [15][16][17][18][19][20][21][22][23][24][25][26][27], including collisional activation to examine fragmentation pathways [18 -23, 25-27]. A few studies have suggested that ion conformation may influence fragmentation pathways [19,23,27,28]. In this paper, we examine this issue for the fragmentation of a series of compact and elongated conformations of ubiquitin ions.…”
mentioning
confidence: 99%
“…The preferred dissociation channels for a peptide or protein ion are highly dependent on the charge state of the ion [40,41] regardless of the dissociation methods employed. Two key factors, number and identities of basic amino acid residues, and the ionization mechanism, play roles in determining the initial charge states of a polypeptide when the ions are formed in the gas-phase via ESI.…”
Section: Charge Increase From a Singly Protonated Peptide To A Doublymentioning
confidence: 99%